Analysis of Palm Biomass Potential for Renewable Energy Sources - Aulia Tama, Dewanda; Syaputra, Widi; Lestari, Fitra (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Heaps of palm oil waste resulting from the rapid development of PKS, causing the risk of environmental pollution, decreased productivity and income of the people living in the factory area. in order to achieve the research objective, namely to find out the opportunities for palm biomass as a renewable energy source using the Composite Performance Index method and later be able to make a decision. Based on the implementation of the research conducted, it was found that only one sustainable biomass was palm shell with a value of 437.5, POME, a value of 425.4 fibers, a value of 367.17 and empty fruit bunches with a value of 343.82.